Religiosity Based Student Discipline Management at SMP Negeri 1 Gunung Jati - Akhmad Hanafi; Indriyani Samba Purwanti; Ike Alvinah; Fika Alimna; Nurhalimah Ramadhani (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2026)
This study aims to describe religious-based student discipline management at SMP Negeri 1 Gunung Jati. The focus of the research includes planning, implementation, and evaluation of the application of religious values in shaping student discipline. The research method used in this study is qualitative with a Systematic Literature Review (SLR) approach, which involves identifying, evaluating, and combining theories and research results. Data collection techniques used in this study include observation, interviews, and documentation. The results of the study show that the integration of religious values, such as routine religious activities, the habit of polite behavior, and character building, has a significant effect on improving student discipline, especially in terms of attendance, compliance with school rules, and academic responsibility. The evaluation is carried out continuously by the school to ensure the effectiveness of the religiosity program in shaping student discipline. Thus, religiosity-based discipline management has proven to be an effective strategy in creating a positive and character-building school culture.